2012
DOI: 10.1080/17458080.2012.661472
|View full text |Cite
|
Sign up to set email alerts
|

Calcium alginate nanocarriers as possible vehicles for oral delivery of insulin

Abstract: In the present investigation, alginate nanoparticles have been prepared and characterised by various techniques such as FTIR, SEM, particle size analysis and surface charge measurements. It was found from both the SEM and particle size analysis that average size of the particle was about 40 nm. The particles were loaded with insulin and the release kinetics of insulin was studied in PBS medium. The results indicated that when percent loading increases from 11.7 to 38.9, the released amount of insulin increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…Around pH 5, the negatively charged carboxylate groups of alginate polymer are electrostatically linked with calcium ions. Since pKa value of alginate lies between 3.4 to 4.4 (Goswami, et al, 2014), the alginate biopolymer will be present as dissociated carboxylate ions around pH 5 facilitating the efficient crosslinking with calcium ions.…”
Section: Formation Of Ferrous Loaded Alginate Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Around pH 5, the negatively charged carboxylate groups of alginate polymer are electrostatically linked with calcium ions. Since pKa value of alginate lies between 3.4 to 4.4 (Goswami, et al, 2014), the alginate biopolymer will be present as dissociated carboxylate ions around pH 5 facilitating the efficient crosslinking with calcium ions.…”
Section: Formation Of Ferrous Loaded Alginate Nanoparticlesmentioning
confidence: 99%
“…According to Goswami et al, the release of insulin from alginate nanoparticles at pH 1.2 was less than 20% while it was 90% at pH 7.4 because at low gastric pH alginate forms a compact acid-gel structure restricting the release of drug from the matrix and also protecting the drug from harsh environmental conditions (Goswami, et al, 2014). Another important factor is that the pKa of alginate lies well above 3.4, hence in very highly acidic medium, alginate remains undissociated protecting the encapsulated drug.…”
Section: In Vitro Release Studies Of Ferrous From Alginate Nanoparticlesmentioning
confidence: 99%
“…Among many different drug‐delivering systems, insulin‐releasing systems, particularly those activated by glucose as the triggering signal are of special interest because of their potential use to treat diabetes mellitus . While numerous synthetic materials have been suggested for controlled delivery of insulin, alginate‐based materials are promising because of their biocompatibility . Indeed, alginate—a natural biocompatible polymer—has been frequently used in many different biomedical applications …”
Section: Introductionmentioning
confidence: 99%
“…[13] While numerous synthetic materials have been suggested for controlled delivery of insulin, [14] alginate-based materials are promising because of their biocompatibility. [15][16][17] Indeed, alginate-an aturalb iocompatible polymer [18,19] -has been frequently used in many different biomedical applications. [20,21] Alginate polymer can be cross-linked with multivalent metal cations (Ca 2 + cations are the most utilized cross-linkers) producingahydrogel capable of encapsulationa nd then controlledr elease of various biomolecules, including proteins/enzymes, [22][23][24][25][26] DNA, [27,28] and other (bio)molecular species, for example,d rugs.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of this delivery system to rats was again shown to lead to better control of blood glucose levels in the animals. Insulin-loaded microgels have also been formed from alginate and calcium using an emulsion-template method [140]. A simulated digestion study showed that the insulin remained trapped inside these particles under gastric conditions, but was released under small intestine conditions.…”
Section: Hormonesmentioning
confidence: 99%